Growth–defense trade‐offs promote habitat isolation between recently‐diverged species - Julia G. Harenčár; Diego Salazar‐Amoretti; Carlos García‐Robledo; Kathleen M. Kay (Ecology and Evolution, 2024)
Abstract Trade‐offs are crucial for species divergence and reproductive isolation. Trade‐offs between investment in growth versus defense against herbivores are implicated in tropical forest diversity. Empirically exploring the role of growth–defense trade‐offs in closely related species' reproductive isolation can clarify the eco‐evolutionary dynamics through which growth–defense trade‐offs contribute to diversity. Costus villosissimus and C. allenii are recently diverged, interfertile, and partially sympatric neotropical understory plant species primarily isolated by divergent habitat adaptation. This divergent adaptation involves differences in growth rate, which may constrain investment in defense. Here, we investigate growth–defense trade‐offs and how they relate to the divergent habitat adaptation that isolates these species. We characterize leaf toughness and chemistry, evaluate the feeding preferences of primary beetle herbivores in controlled trials and field‐based experiments, and investigate natural herbivory patterns. We find clear trade‐offs between growth and defense: slower‐growing C. allenii has tougher leaves and higher defensive chemical concentrations than faster‐growing C. villosissimus. Costus villosissimus has rapid growth‐based drought avoidance, enabling growth in drier habitats with few specialist herbivores. Therefore, growth–defense trade‐offs mediate synergistic biotic and abiotic selection, causing the divergent habitat adaptation that prevents most interspecific mating between C. villosissimus and C. allenii. Our findings advance understanding of ecological speciation by highlighting the interplay of biotic and abiotic selection that dictates the outcome of trade‐offs.